Kesiapsiagaan rumah sakit umum Kabanjahe dalam menaggulangi bencana alam gempa bumi di Kabupaten Karo - Armanda Prima; Andreasta Meliala (Berita Kedokteran Masyarakat (BKM), 2017)
Obstacles and opportunities in making a hospital disaster plan: the case study from North SumateraPurposeThis study assessed Kabanjahe District hospital preparedness in coping with earthquake disaster, describes obstacles and opportunities in forming hospital disaster preparedness and availability of hospital disaster plan component.MethodsThis research used qualitative research method with case study research design. This study examines the contemporary phenomenon of Kabanjahe General Hospital preparedness in anticipating the earthquake disaster.ResultsKabanjahe General Hospital is not ready to anticipate earthquake disaster and not yet completed in making hospital disaster plan.ConclusionObstacles to establishing disaster prepared hospitals to include the unavailability of budget for disaster management, lack of hospital personnel who understand K3B, have not participated in training of hospital disaster plan preparation, disaster training and hospital have never conducted disaster simulation. While the opportunity is Kabanjahe General Hospital has been working with other agencies in the fulfillment of facilities and preparation of the plan. The availability of Kabanjahe General Hospital for policy components, disaster risk analysis, communications, financing and evaluation monitoring has not been in accordance with the standards. As for organizational components and facilities already available in quantity but not yet organized to anticipate disaster.